PENGARUH BIAYA PRODUKSI DAN PENJUALAN TERHADAP LABA BERSIH - Helmiati, Helmiati; Rahmawati, Rahmawati; Putri, Maia Angela (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: In Indonesia there is a trading institution called the Indonesian Stock Exchange (BEI) or Indonesian Stock Exchange (IDX) which started operating on December 1 2007. There are many sectors on the Indonesian Stock Exchange. One of them is the raw goods sector. The raw goods sector consists of several subsectors, including the chemical goods, construction materials, containers and packaging, metals and minerals, and forestry and paper subsectors. As for several raw goods subsectors, forestry and paper companies have quite a large influence on the Indonesian economy. The increasing potential for economic growth and high demand for paper production from forestry and paper subsector companies can affect the profits earned by companies. The factors that influence net profit include production and sales costs. There are several researchers who have conducted research on this raw materials sub-sector. However, there are differences in the results of different studies, such as the research results of Christine Riani (2021) and Muhammad Farhan (2024). Therefore researchers are interested in conducting this research. This is a type of quantitative research with purposive sampling. Data analysis was carried out with SPSS V. 25.This research produces data that production and sales cost variables have a significant effect on net profit in forestry and paper subsector companies listed on the IDX in 2019-2023.Keywords: Production Cost; Sales; Manufacturing Company; Forestry and Paper Subsector; IDX